2017
DOI: 10.1002/mp.12424
|View full text |Cite
|
Sign up to set email alerts
|

Determining the orientation angle of directional leads for deep brain stimulation using computed tomography and digital x‐ray imaging: A phantom study

Abstract: The results show that both imaging modalities can be used to determine lead orientation angles with high accuracy. CT is superior to x-ray imaging, but oblique leads (polar angle > 40°) show limited precision due to the current design of the directional marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 20 publications
3
77
0
2
Order By: Relevance
“…Those results are stable for polar angles of up to 60° (Fig. 4), which signifies a clear improvement compared to previously published methods [10]. The mean deviation in this study was –0.6 ± 1.5° (range: –5.4 to 4.2°) which corresponds to a 6-times lower standard deviation and range compared to the method published by Sitz et al [10] (mean deviation –0.2 ± 9.4°, range: –23 to 34°).…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Those results are stable for polar angles of up to 60° (Fig. 4), which signifies a clear improvement compared to previously published methods [10]. The mean deviation in this study was –0.6 ± 1.5° (range: –5.4 to 4.2°) which corresponds to a 6-times lower standard deviation and range compared to the method published by Sitz et al [10] (mean deviation –0.2 ± 9.4°, range: –23 to 34°).…”
Section: Discussionsupporting
confidence: 64%
“…It was shown that the error induced in the projection values along the line connecting two edges of aligned high-contrast objects is always negative, and thus results in a clearly defined dark streak artifact [19]. While the orientation marker artifact consists of a single dark streak [10], the gaps between the segmented electrodes create a characteristic artifact consisting of six dark streaks (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations